2021
DOI: 10.1093/jamiaopen/ooab063
|View full text |Cite|
|
Sign up to set email alerts
|

Data-driven identification of temporal glucose patterns in a large cohort of nondiabetic patients with COVID-19 using time-series clustering

Abstract: Objective Hyperglycemia has emerged as an important clinical manifestation of coronavirus disease 2019 (COVID-19) in diabetic and non-diabetic patients. Whether these glycemic changes are specific to a subgroup of patients and persist following COVID-19 resolution remains to be elucidated. This work aimed to characterize longitudinal random blood glucose in a large cohort of non-diabetic patients diagnosed with COVID-19. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…In three studies, a matched-cohort study design was used to compare diabetes incidence in a group of participants with previous SARS-CoV-2 infection with a matched control group with no previous infection. In such cases people with prevalent diabetes were specifically excluded at study entry ( 4 , 30 , 34 ). These studies showed that in the cohort of people with previous SARS-CoV-2 infection the incidence of diabetes was higher than the corresponding historical or contemporary non-COVID-19 control cohort, suggesting that infected people might be at higher risk of developing diabetes than people who was not infected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In three studies, a matched-cohort study design was used to compare diabetes incidence in a group of participants with previous SARS-CoV-2 infection with a matched control group with no previous infection. In such cases people with prevalent diabetes were specifically excluded at study entry ( 4 , 30 , 34 ). These studies showed that in the cohort of people with previous SARS-CoV-2 infection the incidence of diabetes was higher than the corresponding historical or contemporary non-COVID-19 control cohort, suggesting that infected people might be at higher risk of developing diabetes than people who was not infected.…”
Section: Resultsmentioning
confidence: 99%
“…Two articles were further excluded because no quantitative data were available after contacting the Authors (16,17). Finally, 20 original paper were included in the review (4,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), with the main characteristics of the studies displayed in Table 1. The detailed selection process is depicted in Figure 1.…”
Section: Studies Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation